2022
DOI: 10.3390/metabo12020176
|View full text |Cite
|
Sign up to set email alerts
|

New Kids on the Block: Bile Salt Conjugates of Microbial Origin

Abstract: Biotransformation of host bile salts by gut microbes results in generation of secondary bile salt species that have biological and physicochemical properties that are distinct from the parent compounds. There is increased awareness that a bile salt–gut microbiome axis modulates various processes in the host, including innate and adaptive immunity, by interaction of microbial bile salt metabolites with host receptors. Omics and targeted approaches have vastly expanded the number and repertoire of secondary bile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…The results herein showed lower levels of primary bile acids in the GI tract of GF mice with a few exceptions in tauro-conjugated primary bile acids which had a higher abundance in this mouse group (i.e., tauro-α/β-muricholic acid, taurocholic acid, and an isomer of taurocholic acid). Mice lacking intestinal bacteria have no deconjugation effect on the amino acid moiety of conjugated primary bile acids, and as they pass through the GI tract, they remain intact 92 . Aligned with this fact, higher abundance of tauro-conjugated primary bile acids in our study may be explained.…”
Section: Discussionmentioning
confidence: 99%
“…The results herein showed lower levels of primary bile acids in the GI tract of GF mice with a few exceptions in tauro-conjugated primary bile acids which had a higher abundance in this mouse group (i.e., tauro-α/β-muricholic acid, taurocholic acid, and an isomer of taurocholic acid). Mice lacking intestinal bacteria have no deconjugation effect on the amino acid moiety of conjugated primary bile acids, and as they pass through the GI tract, they remain intact 92 . Aligned with this fact, higher abundance of tauro-conjugated primary bile acids in our study may be explained.…”
Section: Discussionmentioning
confidence: 99%
“…MBSCs are a novel class of bile acids that are formed by microbial reconjugation of deconjugated/unconjugated bile acids with typically non-canonical amino acids, although host-resembling glycine conjugates can also be generated by microbes [ 27 , 36 , 37 ]. This novel reaction type was previously not suspected to be in the repertoire of bile acid modifications, but has opened the door to discovering new bile acids.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, total bile acid concentration in the colon is between 200–1000 µM where DCA is estimated to be between 10–200 µM [ 24 , 25 , 26 ]. Some of the chemical modification that bile acids will undergo, whilst passing through the gastro-intestinal tract are deconjugation, dehydroxylation, oxidation, epimerization and, most recently, reconjugation [ 26 , 27 ]. The most widespread bile acid modification is the ability to deconjugate bile acids from the amino acid moieties, via microbial bile salt hydrolases (BSH) [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Quinn et al [ 32 ] found novel BAs of cholic acid conjugated to non-canonical amino acids like phenylalanine, tyrosine, and leucine. It has been shown that additional amino acids are coupled to bile acids by microbes [ 33 , 34 , 35 ]. These novel conjugated bile acids have been shown in in vitro experiments to bind to receptors [ 32 ], and therefore are an interesting candidate to be included in bile acid quantification assays.…”
Section: Discussionmentioning
confidence: 99%